On the upward flux of sea‐spray spume droplets in high‐wind conditions. Issue 11 (10th June 2017) - Wu, Lin; Cheng, Xueling; Zeng, Qingcun; Jin, Jiangbo; Huang, Jian; Feng, Yerong
Abstract: It has been speculated that the spume droplets torn off from ocean waves in high wind speeds (larger than about 9 m s −1 ) enhance air‐sea fluxes. However, the vertical transport of spume droplets in the high‐wind atmospheric boundary layer (ABL) is little researched and lacks the support of numerical simulations. Based on observational data and the characteristics of high‐wind ABL above the ocean, the vertical transport of spume droplets is studied and simulated. It is revealed that the existence of gusty wind with coherent structure during high winds is favorable for the vertical transport of the large‐size droplets. The trajectories of 1000 spume droplets with different sizes under different wind speeds in the range 10–35 m s −1 are calculated, and the uplifting fraction of spume droplets that can reach the 100 m height in the ABL is parameterized by using a nondimensional factor U 10 2 /( r 80 g ), where U 10 is the wind speed at 10 m height, r 80 the equilibrium radius of droplet at an equivalent 80% relative humidity, and g the gravitational acceleration. Then, the upward flux of large‐size spume droplets and the mass concentration at 100 m height are evaluated. These numerical results are comparable to some observational data and show that the large‐size spume droplets can be entrained into the ABL during high winds and then contribute to the air‐sea mass fluxes. Key Points: Vertical transports of sea‐spray spume droplets in high winds are studied Sea‐spray spume droplets can fly into the 100 m height with the effects of gusty wind in high winds The effective upward flux and mass concentration of sea‐spray spume droplets at 100 m are estimated